2021
DOI: 10.7554/elife.68335
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning algorithm to translate and classify cardiac electrophysiology

Abstract: The development of induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) has been a critical in vitro advance in the study of patient-specific physiology, pathophysiology and pharmacology. We designed a new deep learning multitask network approach intended to address the low throughput, high variability and immature phenotype of the iPSC-CM platform. The rationale for combining translation and classification tasks is because the most likely application of the deep learning technology we describe here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Discrepancy between highly nonlinear biophysical model responses and linear approximations increases with the severity of the perturbation and increases prediction uncertainty. Recently, a deep learning network approach was demonstrated for translation of immature hiPSC-CM to adult electrophysiology ( 68 ). Comparison of these methodologies may help to determine what portion of all the possible nonlinear electrophysiological mechanisms underlying these biophysical models (and actual myocyte responses in vitro) can be encoded via linear regression and when nonlinear approaches should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancy between highly nonlinear biophysical model responses and linear approximations increases with the severity of the perturbation and increases prediction uncertainty. Recently, a deep learning network approach was demonstrated for translation of immature hiPSC-CM to adult electrophysiology ( 68 ). Comparison of these methodologies may help to determine what portion of all the possible nonlinear electrophysiological mechanisms underlying these biophysical models (and actual myocyte responses in vitro) can be encoded via linear regression and when nonlinear approaches should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that an ECGage that is >8 years greater than the chronological age is associated with a higher rate of mortality [ 82 ]. In 2000, an artificial neural network was used to detect activations during ventricular fibrillation, which resulted in a classification correctness of 92% in the test examples [ 83 ], with improvements having been made since [ 84 , 85 , 86 ].…”
Section: Computer Modelsmentioning
confidence: 99%
“…The spectral power in Gaussian white noise is uniformly distributed across all frequencies and is normally distributed in the time domain. Gaussian noise is one of the most common descriptors of fluctuations in biological systems and is therefore implemented in simulations of ionic currents and EC coupling (e.g., Aghasafari et al, 2021 ; Sato et al, 2009 ; Krogh-Madsen et al, 2017 ; Guevara and Lewis, 1995 ). However, as discussed in further detail below, there is a paucity of analyses of [Ca 2+ ] i and electrical noise during EC coupling and therefore of computational models that incorporate experimentally determined noise; without inclusion of these data, the predictions of these models are altered.…”
Section: Implications Of Noise In Biological Systemsmentioning
confidence: 99%